The effect of sitagliptin on cardiovascular risk profile in Korean patients with type 2 diabetes mellitus: a retrospective cohort study - Shin S; Kim H (Dove Medical Press, 2016)
Sooyoung Shin,1 Hyunah Kim2 1College of Pharmacy, Ajou University, Suwon, 2College of Pharmacy, Sookmyung Women’s University, Seoul, Republic of Korea Background: A 2013 postmarketing study suggested a possible link between saxagliptin use and hospital admission for heart failure. Cardiovascular (CV) effects of sitagliptin, the most commonly prescribed antidiabetic in the same class as saxagliptin, have not been evaluated much in Asian patients with type 2 diabetes. This study sought to ascertain the CV safety of sitagliptin in Korean patients. Methods: A retrospective cohort study of 4,860 patients who were classified into the sitagliptin and metformin groups was conducted using electronic patient data retrieved from a major tertiary care medical center in Korea. Primary composite end points included CV death, myocardial infarction, and ischemic stroke. Secondary composite end points included the aforementioned individual primary outcomes plus hospitalization due to unstable angina, heart failure, or coronary revascularization. A Cox proportional-hazards model was used to compare CV risk associated with drug exposure. Results: Following propensity score (PS) matching in a 1:2 ratio, 1,620 patients in the sitagliptin group and 3,240 patients in the metformin group were identified for cohort entry. The PS-matched hazard ratio (HR) and 95% confidence interval (CI) for sitagliptin relative to metformin were, respectively, 0.831 and 0.536–1.289 (P=0.408) for primary end point and 1.140 and 0.958–1.356 (P=0.139) for secondary end point. Heart failure hospitalization rates did not differ significantly between the two groups, with the PS-matched HR of 0.762 and 95% CI of 0.389–1.495 (P=0.430). When only those patients at high risk of ischemic heart disease were included for analysis, no excess CV risk was observed with sitagliptin compared with metformin. Overall, there were no substantial between-group differences in rates of adverse events, such as hypoglycemia and incident pancreatic disease. Conclusion: Sitagliptin was not associated with elevated risk of CV complications including myocardial infarction, ischemic stroke, heart failure, and coronary revascularization, compared to metformin therapy among Korean patients with type 2 diabetes. Keywords: sitagliptin, dipeptidyl peptidase 4 inhibitors, cardiovascular outcomes, type 2 diabetes